Challenges of independence of internal audit police officers: Evidence from Sudan - Khalid, Azam Abdelhakeem; Ahmed, Waleed Abdelati; Abdalla, Yousif Abdelbagi; Ibrahim, Abdelrahman Mohamed; Ahmi, Aidi (Advance Scientific Research, 2020)
Purpose - This study aims at understanding and explaining the issues related to the independence of internal audit Police Officers at the Ministry of Interior in Sudan. Design/methodology/approach - A qualitative research approach and study case design had been used by this study. Data were gathered through semi-structured interviews, document materials reviews, and observations. Findings - The study found that the application of the independence principle is limited. This is due to the constraint of the command system followed by the Police Force. In spite of that, substantial improvement has been achieved by the internal auditors at the Ministry of Interior in Sudan. The internal audit department is supported by a number of decrees that enhanced its organizational rank and the independence of individual internal audit Police Officers. Practical implications - In view of challenges of internal audit independence police officers, the current case study research contributes to enhancing the limited knowledge about the independence of internal audit practices at the Ministry of Interior in Sudan. This study also adds to the body literature of independence of internal audit by identifying roles, duties and responsibilities of internal audit independence. Originality/value - From the researcher's perspective, this is the first study that aims to understand and explain the issued related to the independence of internal audit police officers at the Ministry of Interior in Sudan.